Analysis of Rural Livelihood Status of Resettled Women: A Case Study in Mullaitivu District - Tharjini, S.; Anushiya, S. (University of Jaffna, 2014)
This study set out to analyse the socioeconomic factors which affect women's contribution to household income and existing livelihood status of resettled women in Mullaitivu district, Sri Lanka. Primary data was used for this study. Purposive and random sampling method was used to select hundred and fifty respondents from this study area. Analysis of data was done by calculating Livelihood status score (LSS, multiple regression analysis and together with descriptive statistics. The descriptive statistic showed that most respondents (62%) were married. Mean age was 41 years, while mean household size was four persons. Most respondents were educated up to secondary level (64%) and not all the respondents were engaged in economic activity. Based on the LSS, it has been shown that overall livelihood status score (seven indicators) was lower for housing condition (10) and higher for water facilities (92). The results of the regression shows that significant factors influencing annual household income of the respondents were age, freedom in cash expenditure, any help from organization, household size, food availability, occupation of respondent, livelihood status score and expense.
Keywords: Household; Livelihood status score; Regression